การหมักแบบเฟดแบตช์เพื่อผลิตกรดจิบเบอเรลลิก - อภิรดี จันทร์ทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purpose of this research was to optimize conditions of gibberllic acid (GA₃) production by Gibberella fujikuroi N9-34 using fed batch fermentation. In preliminary investigation using batch fermentation in a 5 1-fermentor, the result showed that the suitable compositions of medium for gibberellic acid production contained 100g/l sucrose as carbon source, 1.68 g/l (NH₄)₂ and 5.9 g/l defatted soy bean meal as nitrogen source, 5 g/l KH₂PO₄, 1 g/l MgSO₄.7H₂O, 0.1 g/l Al₂O₃ and 0.2% (v/v) soybean oil. Process temperature, aeration rate and initial agitation speed were controlled at 25 ℃, 1 vvm and 600 rpm, respectively. After 24 hrs, the agitation speed was automatically maintained to control dissolved oxygen at 20% of saturated dissolved oxygen throughout the period of fermentation. Under these conditions, the amount of GA₃ produced was 1,203.11 mg/l at 192 hrs. For fed-batch fermentation, the total sugar content was maintained at 40 g/l, with the same condition as batch fermentation, 968.43 and 1,244.43 mg/l of GA₃ were obtained at 192 and 264 hrs, respectively. When controlling the amount of total sugar in the fermentor at 40 g/l and nitrogen at 0.05 g/l between the period of 168-216 hrs by adding (NH4)₂SO₄, the amount of GA₃ was increased to 1,321.44 mg/l at 240 hrs. Therefore, the fed-batch fermentation with a proper controlled level of carbon source and nitrogen source can increase the production of GA₃.